WHISTLEBLOWER PROTECTIONS AND THEIR IMPACT ON REDUCING CORRUPTION IN PUBLIC AND PRIVATE SECTORS - Qasem, Fouad (E-Journal VFU, 2025)
Whistleblower protections are fundamental in mitigating corruption by encouraging individuals to expose unethical practices without the fear of retaliation. This article examines the role of whistleblower protections in both the public and private sectors, focusing on how legal safeguards foster transparency and accountability. By reviewing key legislations such as the U.S. Whistleblower Protection Act (1989), the UK’s Public Interest Disclosure Act (1998), and the EU Whistleblower Protection Directive (2019), it highlights their effectiveness and limitations. Through case studies and empirical research, the article analyzes the positive impact of these protections in uncovering corruption, yet also emphasizes the persistent challenges that whistleblowers face, including retaliation and cultural barriers. The findings underscore the need for stronger enforcement mechanisms, organizational reforms, and cultural shifts to create environments where whistleblowing is supported and protected, ultimately leading to reduced corruption and improved governance [2].